Reducing the risk of venous thromboembolism following superficial endovenous treatment: A UK and Republic of Ireland consensus study. (October 2020) - Dattani, Nikesh; Shalhoub, Joseph; Nandhra, Sandip; Lane, Tristan; Abu-Own, Abdulsalam; Elbasty, Ahmed; Jones, Aled; Duncan, Andrew; Garnham, Andrew; Thapar, Ankur; Murray, Anna; Baig, Anzar; et al.
Objectives: Venous thromboembolism is a potentially fatal complication of superficial endovenous treatment. Proper risk assessment and thromboprophylaxis could mitigate this hazard; however, there are currently no evidence-based or consensus guidelines. This study surveyed UK and Republic of Ireland vascular consultants to determine areas of consensus. Methods: A 32-item survey was sent to vascular consultants via the Vascular and Endovascular Research Network (phase 1). These results generated 10 consensus statements which were redistributed (phase 2). 'Good' and 'very good' consensus were defined as endorsement/rejection of statements by >67% and >85% of respondents, respectively. Results: Forty-two consultants completed phase 1. This generated seven statements regarding risk factors mandating peri-procedural pharmacoprophylaxis and three statements regarding specific pharmacoprophylaxis regimes. Forty-seven consultants completed phase 2. Regarding venous thromboembolism risk factors mandating pharmacoprophylaxis, 'good' and 'very good' consensus was achieved for 5/7 and 2/7 statements, respectively. Regarding specific regimens, 'very good' consensus was achieved for 3/3 statements. Conclusions: The main findings from this study were that there was 'good' or 'very good' consensus that patients with any of the seven surveyed risk factors should be given pharmacoprophylaxis with low-molecular-weight heparin. High-risk patients should receive one to two weeks of pharmacoprophylaxis rather than a single dose.